Derinat® has an immunomodulatory and anti-inflammatory effect on the model of acute lung injury in male SD rats - Palikova, Yulia A.; Palikov, Victor A.; Novikova, Nadezhda I.; Slashcheva, Gulsara A.; Rasskazova, Ekaterina A.; Tukhovskaya, Elena A.; Danilkovich, Alexey V.; Dyachenko, Igor A.; Belogurov Jr., Alexey A.; Kudriaeva, Anna A.; Bugrimov, Daniil Y; Krasnorutskaya, Olga N.; et al. (Frontiers in Pharmacology, 2022)
To simulate acute lung injury (ALI) in SD male rats they we administered intratracheally with lipopolysaccharide (LPS) followed by hyperventilation of the lungs (HVL), which lead to functional changes in the respiratory system and an increase in the blood serum concentration of inflammatory cytokines. LPS + HVL after 4 h lead to pronounced histological signs of lung damage. We have studied the effectiveness of Derinat® when administered intramuscularly at dose of 7.5 mg/kg for 8 days in the ALI model. Derinat® administration lead to an increase in the concentration of most of the studied cytokines in a day. In the ALI model the administration of Derinat® returned the concentration of cytokines to its original values already 48 h after LPS + HVL, and also normalized the parameters of pulmonary respiration in comparison with animals without treatment. By the eighth day after LPS + HVL, respiratory parameters and cytokine levels, as well as biochemical and hematological parameters did not differ between groups, while histological signs of residual effects of lung damage were found in all animals, and were more pronounced in Derinat® group, which may indicate stimulation of the local immune response. Thus, the administration of Derinat® stimulates the immune response, has a pronounced protective effect against cytokinemia and respiratory failure caused by ALI, has immunomodulatory effect, and also stimulates a local immune response in lung tissues. Thus, Derinat® is a promising treatment for ALI.